Third Sector Organisations’ Contributions to the Health and Care Ecosystem - Tuurnas, Sanna; Paananen, Henna; Kork, Anna-Aurora (Ubiquity Press, 2025)
Introduction: In integrated care models, third sector organisations (TSOs) are essential but often undervalued parts of the health and care ecosystem to address care fragmentation and inequity of access. In this study, we illustrate the value contributed by TSOs in a co-production setting. Methods: In this qualitative study, frame analysis was used to explore the varied interpretations of TSOs’ value contributions at different levels of the ecosystem. The qualitative interview data were collected from 16 informants in the context of a Nordic welfare state, Finland. The interviewees represented a variety of health and care TSOs. Results: The resulting frames were seen as organising principles that are socially shared. The analysis revealed a threefold interpretative schema of TSOs’ value contributions: strengthening the ideals of civil society, advancing the public service system and connecting people to communities. Discussion: The findings demonstrate that TSOs contribute values in health and care ecosystems at all levels—micro, meso and macro—by integrating short- and long-term policy objectives, ensuring that their actions result in meaningful and sustainable benefits across all levels of the public service ecosystem. Conclusions: This study underlines the need to integrate civil society into the health and care ecosystem and, specifically, to acknowledge the holistic contribution of TSOs when developing integrated care models. The key contribution of this study is demonstrating the diverse ways in which TSOs can contribute value for integrated care.
Keywords: health and care ecosystems; value contribution; coproduction; third sector organisations; integrated care; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|